Defining high-growth firms in South Africa - Mulalo Mamburu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Traditionally, much of the research on economic growth drivers has been focused on small and medium enterprises. In recent years the academic focus on small businesses has shifted to a particular group of firms that are interesting from an economic growth and policy development perspective, namely high-growth firms. While the standard definition that is recommended by the Organisation for Economic Co-operation and Development is widely accepted, various scholars have used different definitions concentrating on different variables such as turnover or employment growth. Using new South African firm-level data, the study hypothesizes that the identification of high-growth firms is highly sensitive to the measure of firm growth, such that different firm growth measures will return samples of firms with significantly different demographic characteristics. These differences will then have an impact on the findings of analyses based on these growth measures. They will also have implications for public policy recommendations that seek to encourage the emergence of high-growth firms.
Keywords: C33; C38; L25; L26; 330; firm growth; high-growth firms; South Africa; entrepreneurship